2015
DOI: 10.1186/s12933-015-0236-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between daily glucose fluctuation and coronary plaque properties in patients receiving adequate lipid-lowering therapy assessed by continuous glucose monitoring and optical coherence tomography

Abstract: BackgroundGlucose fluctuation has been recognized as a residual risk apart from dyslipidemia for the development of coronary artery disease (CAD). This study aimed to investigate the association between glucose fluctuation and coronary plaque morphology in CAD patients.MethodsThis prospective study enrolled 72 consecutive CAD patients receiving adequate lipid-lowering therapy. They were divided into 3 tertiles according to the mean amplitude of glycemic excursions (MAGE), which represents glucose fluctuation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…Therefore, a drastic alteration in ANA around wake-up would be associated with glucose metabolism and glycemic variability (GV). Recent studies have reported that not only chronic hyperglycemia but daily GV is an independent risk factor for cardiovascular events [12,13]. To our knowledge, no study focusing on the association of the fluctuation in ANA around wake-up on GV has been reported.…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, a drastic alteration in ANA around wake-up would be associated with glucose metabolism and glycemic variability (GV). Recent studies have reported that not only chronic hyperglycemia but daily GV is an independent risk factor for cardiovascular events [12,13]. To our knowledge, no study focusing on the association of the fluctuation in ANA around wake-up on GV has been reported.…”
Section: Introductionmentioning
confidence: 94%
“…The study population consisted of 85% patients with glucose metabolism disorder. In this study, MAGE was the only independent predictor of the presence of TCFA (124). Thus, it may be important to consider MAGE in the treatment of DM by using diabetic agents, such as α-GIs, TZDs, metformin, and incretins, which do not induce hypoglycemia except when administered in combination with sulfonylureas and insulin.…”
Section: Diabetes Mellitus (Dm)mentioning
confidence: 69%
“…Kurihara et al demonstrated that coronary atherosclerosis and plaque vulnerability assessed using angioscopy were more advanced in prediabetic patients than in nondiabetic patients[25]. A recent study showed that glucose fluctuations impact not only atherosclerosis, but also the formation of lipid-rich plaques and thinning of the fibrous cap in CAD patients [26]. In the present study, we performed 75g OGTT in all the patients who had not been diagnosed as DM to specify the patients with IGT and demonstrated that plaque vulnerability was more advanced in CAD patients with IGT than those with NGT using OCT.…”
Section: Discussionmentioning
confidence: 99%